AYURVEDIC MANAGEMENT FOR INTRAUTERINE GROWTH RESTRICTION - A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2020)
Intrauterine Growth Restriction is a major problem affecting pregnant women and results in significant perinatal mortality and morbidity. In the present case a 19-year-old Primi gravida who was under regular ante natal check-up was detected with Intrauterine Growth Restriction at 29 weeks of gestation. The abdominal circumference of the foetus was found to be less than 2.3 percentile and there was oligohydramnios on further evaluation. She was given allopathic management initially, but the condition was deteriorating. She was referred for Ayurveda management and was treated with Ayurvedic medicines considering it as a case of Garbhasosha (foetal emaciation). She was administered Vidaryadi Ghrita internally along with dietary advises. She delivered a healthy female baby of weight 2.97kg at term through Lower Segment Caesarean Section. The scope of modern medicine in improving the baby weight is limited in Intrauterine Growth Restriction. In the present case adequate weight gain of the foetus was achieved in a short span of time thereby preventing the need for early delivery and the pregnancy was continued till 39 weeks of gestation. Being a term delivery the need for neonatal intensive care also did not arise. The current approach indicates that Ayurveda is highly effective in intra uterine growth restriction. This case opens the scope for further research in the area of Intrauterine Growth Restriction with Ayurvedic medicines.